Wien als Blickgewebe. Überlegungen zu Veza Canettis «Die Gelbe Straße»: [Vienna’s interwoven glances. On Veza Canetti’s «Die Gelbe Straße»] (Studia austriaca, 2021)
The following article is focused on the importance of visual perception in Veza Canetti’s Die Gelbe Straße. The novelist portraits a Viennese microcosmos as a fabric in which glances are tightly interwoven, representing an urban way of life that, due to its complexity, demands sharp attention and cunning strategic behaviour from everybody. Canetti aims to challenge all the clichés which praised Vienna as an anti-modern, idyllic capital city, characterizing it as deeply rooted in history and art, and thus more humane. Her novel opposes this idealized vision of her hometown by revealing the pitiless nature of its inhabitants. The multiple ways of looking which may be detected on one street mostly reflect different forms of exerting power in society.